Fish Biodiversity and Water Quality of Tropical Forest Streams Adjacent to the Western Boundary of Kinabalu Park, Sabah: Fish and Water Quality of Sabah Forest Streams - Chen Lin Soo; Hairul Hafiz Mahsol; Leonardo Jainih; Arman Hadi Fikri; Cheng-Ann Chen; Nur Syafiqah Shamsul Kamal (Journal of Tropical Life Science, 2022)
Modification and degradation of habitats outside the boundaries of a national parkmay result in the park's integrity being compromised. Thus, the present study aims todocument variation in freshwater fish and water quality of tropical forest streams adjacent to the western boundary of Kinabalu Park, Sabah. Concurrently, fish samplesand environmental parameters were collected at six stations covering a total streamline length of 10 km. The three most abundant species were Tor tambra (34.4%), Barbodes sealei (19.5%), and Lobocheilos ovalis (12.4%). Tor tambra exhibited a negative allometric growth pattern (coefficient < 3) and was in poor to fair condition (0.8< Fulton’s condition factor < 1.2). The highest fish abundance was found in downstream stations with species addition. Metrics of diversity, such as Shannon's diversityindex and the Margalef index of species richness, decreased as elevation increasedfrom 100 to 600 metres above sea level. The water quality of the forest streams isgood, classified as Class I and/or Class II by Malaysia's National Water Quality Standards, except for ammoniacal nitrogen at station 6, which was classified as Class III.Higher turbidity, orthophosphate, and ammoniacal-nitrogen values were found nearthe Podos village. In conclusion, the altitudinal gradient of fish biodiversity was observed in the forest streams near Kinabalu Park. Regular water quality monitoring ofthe downstream river is necessary, as indicated by the potential domestic impacts onthe river.Keywords: Biodiversity, Elevation, Freshwater fish, Forest stream, Kinabalu Park